EFFECT OF LABOR AND FOREIGN INVESTMENT ON ECONOMIC GROWTH IN INDONESIA - Sawiyah Raudhatul Jannah; Suriani Suriani; Yulindawati Yulindawati (Syiah Kuala University, 2022)
AbstractThis investigation's goal is to examine how foreign investment and labour have an impact on Indonesia's economic development. Quarterly data for the years 2000 to 2020 are the ones that were used. GDP per capita serves as a proxy for economic growth, with labour and foreign investment serving as independent variables. Auto-regressive Distributed Lag (ARDL), which may examine the link between the independent variable and the dependent variable in both the long- and short-term, is the data analysis technique that is utilized. Thus, whereas labour has no effect on economic growth over the long term, it has a negative and considerable impact on it in the short-term economic growth is positively and significantly impacted by foreign direct investment, but long-term effects are negligible.